The impact of financial globalization on output volatility: Panel data evidence for Asian countries - Asma Awan; Nabila Asghar; Hafeez Ur Rehman (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2021)
This study is an endeavor to empirically examine the long run impact of financial globalization on output volatility in a balanced panel of selected 22 Asian countries (full sample) during 1998-2015. The disaggregated analysis is also conducted with respect to Central Asia, East Asia, South Asia and West Asia. The study uses System Generalized Method of Moments for estimation purpose. The results of the study reveal that in overall Asia and Central Asia, financial globalization has emerged as a significant and positive long run determinant of output volatility, whereas insignificance of financial globalization is reported in the context of three sub-samples i.e. East Asia, South Asia and West Asia during reference period. The empirical results appear to be strongly robust in terms of sign, significance and magnitude. To curtail Asia's output volatility this study calls for the use of selective and screened financial globalization during transition phase of building strong institutions. This study is noteworthy as it contributes to limited existing empirical literature on Asia's output volatility. It yields empirical estimates on subject matter in aggregated panel of Asia and in each disaggregated panel of Asia i.e. Central Asia, East Asia, South Asia and West Asia.
Keywords: 330; output volatility; Asia; financial globalization; system GMM